On the rotifer fauna of Disko Island, Greenland, with notes on selected species from a stagnant freshwater lake - Sørensen, Martin V. (Zootaxa, 2006)
The rotifer fauna in Moraine Lake on Disko Island was investigated. 24 species were identified, of which 22 are new for Disko Island and three are new to Greenland. The new findings are presented in a species list that summarizes all records of rotifers from Disko Island, including several previously unpublished records. Furthermore, notes are given on the morphology of some selected species, including Eothinia elongata, Mikrocodides chlaena and Resticula nyssa.